Model Of Recognition Face Spoofing (Texas Journal of Multidisciplinary Studies, 2023)
This article argues model of recognition face spoofing by methods of stream demonstration and Haar cascades. These methods created with comfort and rapidity, can be functional to any face spoofing on program Python, which we use with OpenCV to stream “Motion JPEG” through standard output.